ROBUST DYNAMIC ID-BASED REMOTE MUTUAL AUTHENTICATION SCHEME - Truong, Toan-Thinh; Tran, Minh-Triet; Duong, Anh-Duc (Vietnam Journal of Science and Technology, 2012)
Dynamic ID based authentication scheme is more and more important in insecure wireless environment and system. Two of kinds of attack that authentication schemes must resist are stealing identity and reflection attack which is a potential way of attacking a challenge- response authentication system using the same protocol in both directions. It must be guaranteed to prevent attackers from reusing information from authentication phase and the scheme of Yoon and Yoo satisfies those requirements. However, their scheme can not resist insider and impersonation attack by using lost or stolen smart card. In this paper, we demonstrate that Yoon and Yoo’s scheme is still vulnerable to those attacks. Then, we present an improvement to their scheme in order to isolate such problems.